ChemInform Abstract: Bromopyrrole Alkaloids from Okinawan Marine Sponges Agelas spp. Issue 34 (4th August 2016) - Tanaka, Naonobu; Kusama, Taishi; Kashiwada, Yoshiki; Kobayashi, Jun'ichi
Abstract: Review: 26 refs.